MAPPING THE PERCEIVED GOVERNANCE AND MANAGEMENT CHALLENGES TO PAKISTAN’S GOVERNMENT WITH REFERENCE TO CHINA PAKISTAN ECONOMIC CORRIDOR (CPEC): (A CONCEPTUAL ASSESSMENT) - NISAR, RANA DANISH; HAIDER, WAQAR; AWAN, HADEED SHAHID (The journal of contemporary issues in business and government, 2022)
Under the Chinese-made global harmonious project Belt and Road (BRI) initiative, the China Pakistan Economic Corridor (CPEC) is considered as project of the century which seems reciprocally increase the regional economic integration, economic harmony, rise political sympathetic and has in-depth objectives to change the destiny of the region towards progress, development and mutual win-win wisdom particular reference to Pakistan because Pakistan is the central pillar of this project named CPEC. The CPEC faces several perceived governance as well as management challenges that must be addressed to maximize the project productivity and efficiency. These challenges include political instability, provincial rift, corruption, local oppositions and security concerns. Reciprocally, efforts to address these challenges must involve stakeholders from government, civil society and the private sector and may include reforms to improve transparency and accountability, greater coordination midst different provinces, increase investment in security measures and more effective communication with local communities. Overcoming these challenges is critical to fully leveraging the economic opportunities presented by CPEC and promoting economic growth and development in Pakistan while strengthening ties midst Pakistan and China.